2017
DOI: 10.1016/j.powtec.2016.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Granular mixing in nauta blenders

Abstract: Flow pattern of particles and their mixing performance in a Nauta blender were studied using the discrete element method. The model was validated by experimental data obtained in a convective conical screw blender and good agreement was obtained. Flow pattern of particles was studied through velocity profiles, granular temperature and streamlines of particles. Effects of sweeping rotation speed, primary rotation speed and impeller diameter on the mixing quality and mixing rate were studied. A vertical circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Basinskas and Sakai [55] also concluded that particle loading arrangement was not a crucial parameter when assessing the mixing performance for monodisperse particles in a horizontal ribbon agitated blender. Alian et al [21], Cleary and Sinnott [28], Basinskas and Sakai [55], Golshan et al [56], and Sakai et al [57] investigated the influence of various impeller rotational speeds on the mixing of monodisperse systems. All of the studies above concluded that an increase in impeller rotational speed resulted in enhancing the mixing performance.…”
Section: Mixing Assessment For Mono-disperse Particles Using Demmentioning
confidence: 99%
“…Basinskas and Sakai [55] also concluded that particle loading arrangement was not a crucial parameter when assessing the mixing performance for monodisperse particles in a horizontal ribbon agitated blender. Alian et al [21], Cleary and Sinnott [28], Basinskas and Sakai [55], Golshan et al [56], and Sakai et al [57] investigated the influence of various impeller rotational speeds on the mixing of monodisperse systems. All of the studies above concluded that an increase in impeller rotational speed resulted in enhancing the mixing performance.…”
Section: Mixing Assessment For Mono-disperse Particles Using Demmentioning
confidence: 99%
“…Most of the time, such a distance is positive but it can also be negative if any compression of the cluster occurs. Golshan et al (2017) used a similar criteria to define their tracers. Here, every particle is considered as the center of a cluster.…”
Section: Dispersionmentioning
confidence: 99%
“…Since it is the only method able to consider the discrete aspect of materials, it is well designed to represent the mixing of powders. Thus, sev-eral blender techniques have been investigated through DEM: rotating drums (Mishra et al, 2002;Yang et al, 2008;Liu et al, 2013), screw conveyor-mixers (Hou et al, 2014;Pezo et al, 2015), V-blenders (Lemieux et al, 2007(Lemieux et al, , 2008Kuo et al, 2002), Turbula R (Marigo et al, 2011), static mixers (Pezo et al, 2016) and Nauta blenders (Golshan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…By studying advective transport in the BST flow, we aim to improve the understanding of mixing and transport in systems with combined cutting-and-shuffling and stretching-andfolding motions. This could lead to improvements in industrial mixers with more complicated geometries [38][39][40][41][42][43][44][45][46], especially since many granular mixers would benefit from a mixing mechanism that operates at larger length scales than those associated with diffusion.…”
Section: Introductionmentioning
confidence: 99%